2013
DOI: 10.1002/ajhb.22387
|View full text |Cite
|
Sign up to set email alerts
|

Changes in maternal secretory immunoglobulin a levels in human milk during 12 weeks after parturition

Abstract: The SIgA levels gradually decreased up to week 12. However, the concentration of SIgA in breast milk did not change constantly. It changed relatively rapid until 4 weeks after childbirth, and because the concentration from the third day to the eighth week became 50%, it was understood that the change was temporal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 11 publications
3
28
0
Order By: Relevance
“…Orangutan and gorilla milk contain a lower concentration of sIgA compared with human milk. The concentration of sIgA across gorillas and orangutans, for the first 36 MPP, was 29.5 mg/L which is about 20–30 times lower than the concentrations of sIgA in human mature milk (Goldman et al, ; Kawano and Emori, ; Miller and McConnell, ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Orangutan and gorilla milk contain a lower concentration of sIgA compared with human milk. The concentration of sIgA across gorillas and orangutans, for the first 36 MPP, was 29.5 mg/L which is about 20–30 times lower than the concentrations of sIgA in human mature milk (Goldman et al, ; Kawano and Emori, ; Miller and McConnell, ).…”
Section: Discussionmentioning
confidence: 87%
“…Despite its potential importance, studies evaluating sIgA concentration in non‐human apes are lacking, whereas data regarding sIgA concentration is available for humans from a wide range of populations (Breakey et al, ; Goldman, Garza, Nichols, & Goldblum, ; Hennart, Brasseur, Delogne‐Desnoeck, Dramaix, & Robyn, ; Kawano and Emori, ; Miller and McConnell, ; Olivares et al, ; Smilowitz et al, ; Weaver, Arthur, Bunn, & Thomas, ). In a study of Japanese women, milk sIgA was greater than 2,000 mg/L within a few days of parturition, declining to about 1,000 mg/L by 8–12 wk postpartum (Kawano and Emori, ). Mean milk sIgA values ranged from 308 to 855 mg/L in the study of Toba women (Breakey et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Colostrum, the first breast milk fluid produced in the first five days postpartum, is rich in proteins, such as lactoferrin, immunoglobulins and development factors; its main function is to protect the newborn from infections and promote gut maturation [21••]. One study found the highest immunoglobulin A concentration in the third day after delivery [58]. Transitional milk produced from the sixth day to the second week postpartum is an intermediate fluid with some protective and nutritional properties.…”
Section: Protective Components Of Human Milkmentioning
confidence: 99%
“…In contrast, mature milk (after the fourth week postpartum) has a higher concentration of lipids and lactose, and lower concentration of proteins [21••]. Beyond week 12, the immunoglobulin levels decreased gradually [58]. …”
Section: Protective Components Of Human Milkmentioning
confidence: 99%
“…Kawano and Emori 36 assessed total secretory IgA in human milk and found higher IgA concentrations in the colostrum samples at 72 hours post-partum in primiparous women. In the present study, there were more primiparous women in the control group, but we found higher total IgA concentrations in the case group.…”
Section: Discussionmentioning
confidence: 99%